Perceptions of nursing informatics on quality of nursing practice and competency among nurses in Jordan - Alnajjar, Rami; Zyoud, Amr; Al-Shamaly, Hanan; Tamimi, Abdelrhman; AbedRabbu, Moath (Frontiers in Digital Health, 2025)
BackgroundThe application of nursing informatics and its specific components, such as the EHR/EMR comes with an array of positive implications. However, these benefits are poorly explored in Jordan as a country where digitized nursing information still struggles through challenges.ObjectivesThis research was conducted to examine the perceptions on the nursing informatics towards quality of clinical nursing practice, and to determine how nursing informatics affect clinical competency among nurses.MethodsQuantitative research was conducted between September 2018 and May 2023. Data was collected using a research questionnaire administered to 256 clinical nurses in three government hospitals in Amman government, Jordan. The hospitals that were part of the study are the following: Prince Hussein bin Abdullah Hospital, Al-Bashir Hospital and Dr. Jamil Al-Totangi Hospital. Analysis of data was done using SPSS (version 26) and SPSS-AMOS.ResultsThe respondents expressed that nursing informatics ensures a quality of clinical nursing practice in clinical nursing care plan, use of nursing informatics, quality of patient care, clinical nurse's competency and patient safety. Further statistical analysis showed that that there is a statistically significant effect of nursing informatics on the competency of clinical nurses (p = .001; β = .547).ConclusionNursing informatics has various significant benefits that relate to quality of clinical practice and nurses' competency, as perceived by the Jordanian clinical nurses.RecommendationComprehensive adoption of nursing informatics in Jordanian hospitals may help improve the overall quality of patients' care.